Single, composite, and ceramic Nd：YAG 946-nm lasers - 兰瑞君 阳光 王正平 (Chinese physics B, 2015)
Single, composite crystal and ceramic continuous wave （CW） 946-nm Nd：YAG lasers are demonstrated, respectively. The ceramic laser behaves better than the crystal laser. With 5-mm long ceramic, a CW output power of 1.46 W is generated with an optical conversion efficiency of 13.9%, while the slope efficiency is 17.9%. The optimal ceramic length for a 946- nm laser is also calculated.